النقد الإجتماعي في الشعر الشعبي علي عناد نموذجا مقاربة حجاجية - فطحيزة علي, الحسين; عطاء الله, معتز بالله (University of Eloued جامعة الوادي, 2024)
إهتم الشعر الشعبي مثل نظيره النخبوي بالقضايا الاجتماعية، وعالجها جملة وتفصيلا، مثل المشاكل الأسرية ومسائل الأخوة وكذا الآداب العامة من أخلاق وتعاون وإيثار وإتحاد. وقدمها في قوالب جميلة جذابة و مؤثرة، تناسب مستوى المتلقين وذوقهم، منسجمة مع الأعراف والعادات المحلية، والشاعر علي عناد نجح في هذا المجال، فقد وظف شعره في النقد الاجتماعي والتوجيه، مستغلا طاقات اللغة وبلاغتها وتصويرها ساعيا لتوصيل رسالية الشعر الشعبي بالتفاعل مع كل الأوضاع ومعالجة مختلف القضايا، مخلفا أثرا بالغا على السامعين، ليساهم في ترسيخ ثوابت المجتمع داعيا إلى المحافظة عليها، فاتحا الباب للدارسين لتناول إنتاجه وتطبيق مختلف النظريات الأدبية والاستفادة منها. Folk literature, like its elite counterpart, has addressed social issues thoroughly, including family problems, brotherhood matters, and general moral theme such as ethics, cooperation, altruism, and unity. It presents these in beautiful, appealing, and impactful forms tailored to the audience's level and taste, thus aligning with local customs and traditions. Poet Ali Anad has succeeded in this realm by using his poetry for social criticism, guidance, and education. In order to promote the power and eloquence of language and its imagery, he aims to convey the message of folk poetry by engaging with all situations and addressing various issues, leaving a positive impact on listeners. His work contributes to reinforcing the nation's values, stressing their preservation, and opening doors for scholars to analyse his output and apply various literary theories for better understanding.
دراسات أدبية
Keywords: النقد الاجتماعي، الشعر الشعبي، مقاربة حجاجية.; social criticism; popular poetry; argumentative approach.